Men and Trolls: A Discussion of Race and the Depiction of the Sámi in the Hrafnistumannasögur - Thysse 陳藹文, Arwen (Scandinavian-Canadian Studies / Études scandinaves au Canada)

(untitled) (Association for the Advancement of Scandinavian Studies in Canada, 2022)
This article discusses the often stereotyped and essentialized depiction of the Sámi in Old Norse sources in light of recent work on critical race theory and its application to the Middle Ages. Focussing on the portrayal of Sámi characters in the late-medieval Hrafnistumannasögur (Sagas of the Men of Hrafnista), this article argues that Norse portrayals of the Sámi were racial in character and that there did indeed exist a racial dynamic between the two peoples, at least during the late-medieval period from which these sagas survive. Consideration is also given towards how both positive and negative portrayals of the Sàmi in these sources can be understood within a racialized context. This article is a winner of the 2022 Marna Feldt Graduate Publication Award.